The Trajectory of Concurrent Motor and Vocal Behaviors Over the Transition to Crawling in Infancy. (13th March 2017) - Berger, Sarah E.; Cunsolo, Marian; Ali, Mariam; Iverson, Jana M.
Abstract : To document the trajectory of motor and vocal behaviors in real and developmental time, we observed infants at each of four biweekly naturalistic play sessions over the transition to crawling. An exhaustive and mutually exclusive coding scheme documented all vocalizations and postures. Odds ratios of the likelihood of a given posture‐vocalization dyad revealed that vocalization and crawling were significantly unlikely to co‐occur at the session marking the onset of crawling. We speculate that infants' allocation of attention over the transition to crawling prompted behavioral trade‐offs. During mastery of a novel skill, infants may have had difficulty allocating attention to multiple tasks, but with experience, a decrease in attentional load for the new skill allowed performance of simultaneous behaviors in other domains to occur.